Wildlife Diversity and Population Status of Kashimpur Union, Gazipur, Bangladesh - Islam, Nazmul; Jaman, M Firoj; Rahman, Md Mokhlesur; Alam, Md Mahabub (Journal of the Asiatic Society of Bangladesh, Science, 2018)
Wildlife diversity (amphibians, reptiles, birds and mammals) of Kashimpur Union in Gazipur Sadar Upazila under Gazipur district was studied from May, 2015 to March, 2016. A total of 110 species of wildlife belonging to 58 families under 19 orders were recorded. Among them, 6 (5.45%) species were amphibians, 14 (12.72%) reptiles, 72 (65.45%) birds and 18 (16.38%) were mammals. Among the amphibians, 5 (83.33%) species were frogs and only one (16.67%) was toad; of reptiles, 7 (50%) species were lizards, 5 (35.71%) snakes and 2 (14.29%) were tortoises. Of the birds, 39 (54.16%) species were passerines and remaining 33 (45.84%) were non-passerines. Resident status shows that 66 (91.62%) species were resident, 5 (7.00%) migrants and 1 (1.38%) species were vagrant. Among the mammals, 8 (44.45%) species were rodents, 4 (22.22%) flying mammals and 6 (33.33%) species were carnivorous mammals. The relative abundance shows that 10 (9.09%) species were very common, 24 (21.81%) common, 31 (28.19%) fairly common and 45 (40.91%) species were few. Considering the conservation status, 5 species were near threatened and 105 were the least concern nationally. According to Shannon-Wiener (H = 3.287) and Simpson's (D = 0.942) diversity indices, diversity of birds was higher than the other wildlife observed. Some potential threats on wildlife diversity were identified such as habitat degradation and fragmentation, expansion of agricultural lands and urbanization. Therefore, conservation and management are necessary in order to protect the diversity of existing wildlife and their population in the study area. Asiat. Soc. Bangladesh, Sci. 44(2): 101-115, December 2018